Tobacco: An invisible and immediate threat for COVID 19 - Garg, Suneela; Deshmukh, Chetna (Indian Journal of Community Health, 2020)
One of the major steps to prevent damage due to any pandemic is to focus on risk factors related to the disease. Tobacco consumption is emerging as a major factor out of all for COVID 19. There is hardly any country who has warned the public about this or has made the Tobacco control measures stringent in view of COVID 19. Factors making tobacco consumers more vulnerable to COVID 19 infections are low immunity, damaged cilia in smaller air ways leading to decreased lung capacity and previous history of respiratory illness. Smokers have more expression of ACE2 receptor gene which is also responsible for SARS-COV-2 virus replication in host. More viral load makes smokers potent “carrier”. COVID 19 can be transmitted via tobacco consumers by sharing of smoked tobacco and release of vapour droplets. Spitting of smokeless tobacco in public places puts community at risk. Cardiovascular diseases and cancers caused by tobacco consumption act as comorbidities aggravating the symptoms in COVID 19 infection. Scope of FCTC framework can be extended to address prevention and control of COVID 19. Recommendations: tobacco products should be banned immediately to control the spread. MPOWER strategy of FCTC can be utilized in this pandemic to prevent transmission.